Processos educativos da infância em Cuiabá (1870-1890) - Ana Paula da Silva Xavier (2012)
The aim of this thesis is the study of the educational process of children of different social and ethnic-racial background in Mato Grosso, more specifically in Cuiabá, from 1870 to 1890. This enables us to question the educational projects and the configuration of different spaces and educational strategies in Mato Grosso, in the late nineteenth century. The main goal is to show the educational experience of different children, in order to highlight the plurality of their social and ethnic-racial background of the subjects, the different styles and the educational spaces that existed in that time. To discuss the social relationships experienced by children in Mato Grosso and the educational experiences that result from the relationship established between the different social background, in the nineteenth century, this research establishes a field observation, the urban area of Cuiabá, focusing on the parishioners of the Sé cathedral (Senhor do Bom Jesus parish), also known as 1st District. On the one hand, this spatial demarcation is related to the difficulty of collecting and analyzing data related to the demographic contingent and to the public education throughout the municipality of Mato Grosso. On the other, the delimitation of this social field, in a circumscribed scope, enables locating and give visibility to the individual experience of learning different subjects. This research has focused two central issues that contribute to think of the social and ethnic status of the subjects and their respective educational experiences. One may question: What is the relationship between different social groups and school education in Mato Grosso in the late nineteenth century? Besides the school, what are the possible spaces and educational strategies experienced by school children in Cuiabá? These issues are discussed in the light of a diverse set of sources consulted throughout the investigation. The documental corpus of this research is formed by sources census, school maps, legislation in force in the school period; official records (reports and correspondences) linked to the Presidency of the Province, to the General Directorate of Public Education and the Directorate General of Indians of Mato Grosso; as well as travelers accounts and the memories of people who experienced the daily life of Cuiabá. Among these sources, one should note the school maps, sources from census and the memoirs, being still little used in research in the History of Education, as well as contributing, significantly, to bring up the subjects of educational action. Based on this set of documents, this Thesis presents three case studies that include school and non-school experiences. When presenting the educational trajectory of three research subjects, it is intended, on the one hand, to contribute to the understanding of the construction of the socio-ethnic-racial identity and the possible modes of education experienced by the subjects in school age, amid the social relationships of the nineteenth century. On the other, it seeks to contribute to the rewriting of the history of education, when analyzing the educational process of children from different socio and ethnic-racial social background, considering them as historical subjects.